Fallbuch Asylrecht Mit Bezügen zum Aufenthaltsrecht - Mantel, Johanna; Nachtigall, Rhea; Wasnick, Lars (De Gruyter Studium, 2023)
This case book examines the facts of asylum law most relevant to practice and their relationship to residence law in 57 case studies. A team of emerging scholars, practitioners, and members of Refugee Law Clinics (RLCs) has compiled practical case studies for advisors, law students, and trainee lawyers. Readers can comment on all cases on a digital platform.